Research on Intelligent Materials in the Civil Engineering Field - Huang, Yaqi (Transactions on Engineering and Technology Research, 2024)
With the continuous development of civil engineering technology, the requirements for material properties are getting higher and higher, and intelligent materials have attracted much attention as a new field. Based on the background of civil engineering, this paper discusses the research progress of four intelligent materials: carbon fiber concrete, nano carbon black concrete, shape memory alloy (SMA)and piezoelectric materials. The performance characteristics, application advantages and shortcomings of these four materials in civil engineering are mainly studied. Through comparative analysis, the excellent properties of carbon fiber concrete in terms of strength and durability, the significant improvement of mechanical properties and electrical conductivity of nano carbon black concrete, the unique advantages of SMA in earthquake self-healing, and the important role of piezoelectric materials in structural health monitoring are revealed. The conclusion shows that although intelligent materials show great potential in performance, problems such as cost, process and performance stability remain to be solved. The research in this paper not only enriches the research system of civil engineering materials, but also provides theoretical reference and practical guidance for the wide application of intelligent materials in civil engineering in the future.